2007
DOI: 10.1007/s00428-007-0526-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of stromal MMP-1, MMP-9 and TIMP-1 in basal cell carcinomas of immunosuppressed patients and controls

Abstract: Matrix metalloproteinases (MMPs) have an important role in the initiation, growth, and invasion of malignant tumors. Basal cell cancer (BCC) is the most common human malignancy. The risk of BCC is 10-16 times higher among organ transplant recipients compared with the nontransplanted population. The aim of this study was to compare the expression of several MMPs and their tissue inhibitors (TIMPs) in BCCs from kidney transplant recipients and controls. Expression of MMPs-1, -7, -8, -9, -10, -13, -26, and TIMPs-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 48 publications
1
29
1
Order By: Relevance
“…This result was also in agreement with that of Boyd et al [27]. In the current study, there was a statistically significant relationship between MMP-9 expression and the histopathological grade of SCC cases.…”
Section: Figure 10supporting
confidence: 95%
See 1 more Smart Citation
“…This result was also in agreement with that of Boyd et al [27]. In the current study, there was a statistically significant relationship between MMP-9 expression and the histopathological grade of SCC cases.…”
Section: Figure 10supporting
confidence: 95%
“…Kerkelä et al [25,26] previously reported that stromal cells are the major source of MMPs. Boyd et al [27] reported that MMP-9 was not detected in the BCC epithelium, but in neutrophils and macrophages surrounding it. Whether this strong stromal Well-differentiated squamous cell carcinoma with intense stromal and epithelial positivity for matrix metalloproteinase-9 (MMP-9) (immunoperoxidase for MMP-9, Â 100).…”
Section: Discussionmentioning
confidence: 97%
“…Such basement-membrane deposition is an early event during wound healing of the skin, whereby a keratinocyte monolayer moves across provisional wound matrix and deposits a basement membrane in cooperation with dermal fibroblasts (Friedl and Gilmour, 2009). Likewise, in epithelial cancers such as oral cancer and basal cell carcinoma, collective invasion occurs along an intact basement membrane, yet the role of the basement membrane in favouring or counteracting collective invasion is not clear (Bauer et al, 2008;Boyd et al, 2008).…”
Section: Deposition Of a Basement Membranementioning
confidence: 99%
“…Tumor cells secrete MMPs and induce stromal cells to produce MMPs [4,5]. MMP-2 and MMP-9 are proteolytic enzymes with a major role in type IV collagen digestion, an important event in vascular invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…TIMPs are multifunctional proteins that not only inhibit MMPs but also promote cell growth, induce apoptosis, and inhibit angiogenesis [5,7]. However evidence suggests that TIMPs, in particular TIMP-1 and TIMP-2, may have unique biological properties, independent of their ability to inhibit MMPs [8].…”
Section: Introductionmentioning
confidence: 99%